Sensing node selection and mobile sink displacement in the environments with multiple targets - Leila Saadatdoost; Homayun Motameni; Seyed Mehdi Hosseini Andargoli; Reza Ghazalian (IET Wireless Sensor Systems, 2021)
Abstract In target tracking scenarios, a suitable sensor selection method in combination with designing mobile sinks (MSes) movement path is a promising solution to maximise the lifetime of the wireless sensor network (WSN). The lifetime optimization problem is non‐deterministic polynomial‐time hardness (NP‐hard) and its optimal solution requires an exhaustive search with the exponential complexity. To tackle this issue, the original problem is separated into two more tractable sub‐problems: first, the MSes' assignment and their positions' calculations, second, the SN assignment problem. The SNs assignment problem is an integer programing, which is relaxed to the more tractable form. Moreover, its solution results in a priority function which is combined with a numerical search algorithm to select the SNs. In the proposed framework, based on the estimated path of each target, a MS is assigned to the target. Besides, the MSes optimum position in the next rounds are calculated. Afterwards, for each target at each round, sensing nodes (SNs) are selected based on the targets' position and the MSes' position. Simulation results show that proposed solution increases the network's lifetime considerably in comparison with the benchmark algorithms while its complexity is much lower than that of the optimal exhaustive search algorithm.